Performance of the Frequency-Response-Shaped LMS algorithm in impulsive noise - Ahmad, Mohammad Shukri; Hocanin, Aykut; Kukrer, Osman (My University, 2007)
The performance of the Frequency-Response-Shaped Least Mean Square (FRS-LMS) adaptive algorithm in estimating a sinusoidal signal in impulsive and correlated noise is investigated. The algorithm does not require a priori knowledge about the nominal Gaussian process and is able to adapt to changes in the environment. The performance of the FRS-LMS is compared to that of the Leaky-LMS algorithms in terms of Mean Square Error (MSE) and convergence speed. The results indicate that while the FRS-LMS and the Leaky LMS algorithms perform similarly in AWGN, the FRS-LMS provides superior performance in impulsive and correlated noise environments. The performance gain is due to the frequency shaping and outlier reduction properties of the algorithm. © 2007 IEEE.
2007 IEEE International Conference on Signal Processing and Communications, ICSPC 2007 --
Keywords: Correlated noise; FRS-LMS; Impulsive noise; Leaky-LMS